KOMPETENSI PUSTAKAWAN DALAM MELAYANI SISWA TUNAGRAHITA DI SLB BINA ANAK BANGSA PONTIANAK - Rizilda Rizilda; Atiqa Nur Latifa Hanum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research is supported by the author's desire to know the competence of the librarian in serving the students at the library of the SLB Bina Anak Bangsa. The aim of this final task is to explain the importance of librarian competence in serving the students and know how to serve the students in the library of Bina Anak Pontianak SLB. In this research researchers use a descriptive method with a qualitative approach form. Data collection techniques are done through observation, interviews, and documentation conducted by the researcher on the one informant is librarian in the library SLB Bina Anak Bangsa Pontianak. The results of this study showed that the service to the students has fulfilled the competence of service and librarian is in the process of optimizing in conducting services to the students of the disabled in the library SLB Bina Anak Bangsa Pontianak. The service provided to the general students differs from the students Tunagrahita, therefore the librarian must be able to communicate, be gentle, and be attentive in serving and provide the information required by the students of Tunagrahita.Keywords : Competence, Librarian, Student Disabled.